2008
DOI: 10.3354/dao01905
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of Salmonella spp. among marine animals in the Channel Islands, California

Abstract: Salmonella enterica is a zoonotic pathogen that has been isolated from free-ranging marine mammals throughout the world, with animals in the Channel Islands of California (USA) showing the highest prevalence. The goal of this study was to determine prevalence, antimicrobial sensitivity and genetic similarity using pulsed-field gel electrophoresis (PFGE) of Salmonella in several non-domestic animal species on San Miguel and San Nicolas Islands. Fecal samples were collected from 90 California sea lion Zalophus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…The correlation observed between Salmonella and cEC in beach sands may suggest that these microorganisms originated from similar sources (26,53). Moreover, the lack of association between the HF marker, Salmonella, and Campylobacter in sand was suggestive of nonhuman sources of these pathogens in beach sand, such as marine birds and mammals (44,64). The microcosm studies demonstrated that the HF marker was long lived in beach sand ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation observed between Salmonella and cEC in beach sands may suggest that these microorganisms originated from similar sources (26,53). Moreover, the lack of association between the HF marker, Salmonella, and Campylobacter in sand was suggestive of nonhuman sources of these pathogens in beach sand, such as marine birds and mammals (44,64). The microcosm studies demonstrated that the HF marker was long lived in beach sand ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance in the isolates was very rare, in dramatic contrast to the situation reported in another paper in this issue for isolates of diverse other bacteria from free-ranging marine mammals on the US NE coast (Bogomolni et al 2008). Stoddard et al (2008) caution people handling such animals to be aware of the zoonotic risk, especially in California, where the prevalence seems unusually high, and they discuss the potential sources of these Salmonella infections in terms of island land-mammal populations.…”
mentioning
confidence: 64%
“…The Stoddard et al (2008) study documents a high prevalence of a variety of Salmonella serovars with zoonotic potential in sea lions and elephant seals in the Channel Islands, California, USA, but a much lower prevalence of serovars in Puget Sound, Washington, USA. Antibiotic resistance in the isolates was very rare, in dramatic contrast to the situation reported in another paper in this issue for isolates of diverse other bacteria from free-ranging marine mammals on the US NE coast (Bogomolni et al 2008).…”
mentioning
confidence: 92%
“…It is also important to mention that many of the serovars isolated from seagulls showed an intermediate sensitivity according to the Kirby-Bauer qualitative method of susceptibility, but susceptibility to them will depend on which species will be infected by these serovars. It was reported that 9% of seagulls (Larus occidentalis) studied, in 2008, in California were carriers of Salmonella but only from one of those seagulls an antibiotic resistant Salmonella was isolated [32]. Subsequently, was reported a 24% (n = 216) isolation of Salmonella from young blackheaded gulls (Larus ridibundus) being S. Enteritidis (PT 8 and 4) the most prevalent showing a 28% of resistance to antibiotics [33].…”
Section: Smentioning
confidence: 99%